Konsep Psikologi Dalam Perspektif Pendidikan Islam - Muchamadun, Muchamadun (Al-Riwayah : Jurnal Kependidikan, 2016)
Lately there are various problems faced by humans. The problems are the socio-economic gap that does not give a sense of unease or uncomfortable, both in terms of physiological and psychological, which both bring negative result. Humans have a duty to endeavor in order to find a cure for the disease. Complication of physical illness due to psychological conditions can be caused by mental illness, which is often known as psychosomatic (from body pain caused by mental illness). Therefore, the need for relief efforts for those who have psychiatric disorders (neurosis) or mental illness (psychosis) as a result of frustration to face the reality of life. This paper seeks to provide therapeutic solutions that are based on Quran